Ergonomic Assessment and Musculoskeletal Health of the Underpri¬vileged School Children in Pune, India - Pavithra Rajan; Anand Koti (Tabriz University of Medical Sciences, 2013)
Background: Musculoskeletal health in schoolchildren is a global health problem. The objective of the current study was to assess ergonomic be¬havior and muscu-loskeletal health in urban poor schoolchildren in Pune, India. Methods: Sixty-five (29 male students) slum dwelling schoolchildren were assessed for their ergonomics using a validated and reliable tool. Results: Average age was 13 years. Out of 65 students, 36 reported pres¬ence of musculoskeletal pain. In addition, 78.5% had bad ergonomics when lifting books. Sitting posture was poor in 67.7%, while 50.8% dem¬onstrated bad posture while using a computer. As far as the female stu¬dents were concerned, it was seen that out of 36 students, 55.6% com¬plained of presence of pain. Out of the 20 students who reported pain, 70% had a score lower than 7.5 on ergonomic score assessment (indicative of bad ergonomics). When the male students were considered, out of 29 students, 65.5% reported presence of pain. Out of the 19 students who reported pain, close to 79% demonstrated bad ergonomics. Conclusion: There is presence of musculoskeletal aches and pains in this under-privileged section of the society, including demonstration of bad er¬gonomics and postures while performing activities in school. Thus, mus¬culoskeletal health prob-lems exist in urban slum schoolchildren. It is im¬portant to identify health problems at an early stage in both boys and girls. Children are the future of the nation and hence, identification of health issues early in life and preventing them from becoming chronic is of utmost importance.